Para f(x) = 2x4 - x3 + 2x2 - 5 , calcule P = f’(2) + f’(-1) .
Soluções para a tarefa
Respondido por
6
Oi. Eu faria assim:
f'(x)=8x³-3x²+4x
f'(2)=8·2³-3·2²+4·2
f'(2)=64-12+8
f'(2)=60
f'(-1)=8·(-1)³-3·(-1)²+4·(-1)
f'(-1)=-8-3-4
f'(-1)=-15
P = f’(2) + f’(-1)
P= 60+(-15)
P= 45
Eu faria isso. Espero que tenha ajudado.
f'(x)=8x³-3x²+4x
f'(2)=8·2³-3·2²+4·2
f'(2)=64-12+8
f'(2)=60
f'(-1)=8·(-1)³-3·(-1)²+4·(-1)
f'(-1)=-8-3-4
f'(-1)=-15
P = f’(2) + f’(-1)
P= 60+(-15)
P= 45
Eu faria isso. Espero que tenha ajudado.
julianacamelo:
obg!
Perguntas interessantes